A Study on the Environmental Technological Innovation Strategy of a Malaysian Firm - Fakhrul Yusuf, Muhammad; Ashari, Hasbullah; Rizal Razalli, Mohd (International Journal of Engineering and Technology, 2018)
Firms all over the world have pursued sustainable development to be competitive in the marketplace. The purpose of this case study is to examine the factors that enable a firm to pursue the environmental technological innovation (ET-innovation) strategies and how it effectively leverages its resources to achieve the environmental and business targets. This case study also wants to understand how well the firms ET-innovation activities can be explained by stakeholder theory, resource-based view and dynamic of innovation model. This paper uses a qualitative approach and the coding analysis was done on QSR NVivo. The data collection was done through interviews and also compared with other data sources (company brochures, reports, letters, speeches, memos, videos, newspaper articles, trade magazine articles, magazines articles, reports, website articles and technical reports) for triangulation purposes. This research showed that the ET-innovative firm in this case study has leveraged their employee technical abilities to be successful in their respective market. Another factor is the owner’s high interest in innovation and environmental protection, and involvement in the design and marketing of their eco-product. Despite stakeholders’ different targets, the case study firm manages to acquire support from their stakeholders through common objective which is to see a successful ET-innovation. Finally, it is proposed for the firm to be aware of the dynamics of eco-product lifecycle while also use current tools to manage their eco-product development especially in the earlier development stage.